2018
DOI: 10.1177/2047487318766954
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy in familial hypercholesterolemia: A cross-national study

Abstract: Background High rates of inadequate health literacy are associated with maladaptive health outcomes in chronic disease including increased mortality and morbidity rates, poor treatment adherence and poor health. Adequate health literacy may be an important factor in the effective treatment and management of familial hypercholesterolemia, and may also be implicated in genetic screening for familial hypercholesterolemia among index cases. The present study examined the prevalence and predictors of health literac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
4
31
0
2
Order By: Relevance
“…The association between education and health literacy levels was the primary focus of this study, that is, health literacy is associated with educational level. This result is consistent with the survey on health literacy in familial hypercholesterolemia showing educational level-related variations in health literacy [24]. The participants with higher education possibly had additional learning opportunities and thus, additional knowledge.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The association between education and health literacy levels was the primary focus of this study, that is, health literacy is associated with educational level. This result is consistent with the survey on health literacy in familial hypercholesterolemia showing educational level-related variations in health literacy [24]. The participants with higher education possibly had additional learning opportunities and thus, additional knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed that the related health benefits and services of economically disadvantaged groups were less likely to be accessed than those of economically affluent groups [27,28]. Therefore, the income level is possibly one of the economic determinants linked to health literacy among patients with chronic diseases [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, optimisation of anti-atherosclerotic strategies should rely on the inhibition of both risk factors to limit the residual risk demonstrated by currently used drugs. 34 In patients with FH, reduction of inflammatory risk seems to be harder to obtain than in other patients at increased cardiovascular risk, thus additional pathophysiological studies are warranted to clarify the peculiar ‘resistance’ of atherosclerotic inflammation in FH patients. 35 With this point of view, FH subjects could particularly benefit from the addition of selective anti-inflammatory compounds on top of the already recommended lipid-lowering drugs to blunt atherosclerotic burden and improve cardiovascular outcome.…”
mentioning
confidence: 99%
“…In this study, we did not assess whether machine-learning models can replace the Dutch Lipid Score at a population level, which can be the subject of further studies as FH is probably underdiagnosed and untreated. 22,23…”
Section: Discussionmentioning
confidence: 99%